2020
DOI: 10.1055/s-0040-1710300
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Preeclampsia, Advanced Maternal Age and Maternal Obesity in Neonatal Outcomes Among Women with Gestational Diabetes

Abstract: Objective The present study aims to analyze adverse fetal or neonatal outcomes in women with gestational diabetes, including fetal death, preterm deliveries, birthweight, neonatal morbidity and mortality, as well as the synergic effect of concomitant pregnancy risk factors and poor obstetric outcomes, as advanced maternal age, maternal obesity and pre-eclampsia in their worsening. Methods The present cohort retrospective study included all pregnant women with gestational diabetes, with surveillance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…PE is the main cause of maternal and fetal mortality and morbidity (19,20). GDM complicated by PE further increases perinatal adverse events (21)(22)(23)(24), future maternal risk of chronic hypertension, cardiovascular disease, and diabetes (25)(26)(27); offspring body mass index (BMI) also steadily increases over time (28). Identifying factors associated with occurrence of PE in women with GDM, especially those that are controllable, is important for improving pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…PE is the main cause of maternal and fetal mortality and morbidity (19,20). GDM complicated by PE further increases perinatal adverse events (21)(22)(23)(24), future maternal risk of chronic hypertension, cardiovascular disease, and diabetes (25)(26)(27); offspring body mass index (BMI) also steadily increases over time (28). Identifying factors associated with occurrence of PE in women with GDM, especially those that are controllable, is important for improving pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Nunes et al investigated the influence of PE, advanced maternal age, and maternal obesity on neonatal outcomes in patients with GDM. They found that among these three factors, only the coexistence of PE showed an association with adverse neonatal outcomes, such as neonatal morbidity, low and very low birthweight, and preterm delivery [ 24 ]. To our knowledge, there is only one study comparing perinatal outcomes in patients with hypertensive disorders of pregnancy (HDP) with and without GDM.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of developing PE in patients with GDM has been, up to date, widely studied [ 22 , 23 , 24 , 25 ]. PE and GDM share several risk factors, such as advanced maternal age, nulliparity, multiple pregnancy, ethnicity, and pregestational obesity.…”
Section: Introductionmentioning
confidence: 99%
“…IMT pregestasional merupakan faktor risiko terjadinya komplikasi maternal dan perinatal. 8 Peningkatan IMT ibu dikaitkan dengan luaran peningkatkan biaya perawatan kebidanan, termasuk peningkatan angka persalinan dengan seksio sesarea, morbiditas ibu, penggunaan neonatal intensive care unit (NICU), dan lama perawatan di rumah sakit. 9 Obesitas ibu juga dikaitkan dengan peningkatan risiko morbiditas neonatal seperti kelahiran pada usia kehamilan <33 minggu, berat lahir > 4000 g, cedera lahir, skor Apgar yang lebih rendah, sindrom gangguan pernapasan, sepsis bakteri, kejang neonatal, dan hipoglikemia.…”
Section: Pendahuluanunclassified
“…9 Obesitas ibu juga dikaitkan dengan peningkatan risiko morbiditas neonatal seperti kelahiran pada usia kehamilan <33 minggu, berat lahir > 4000 g, cedera lahir, skor Apgar yang lebih rendah, sindrom gangguan pernapasan, sepsis bakteri, kejang neonatal, dan hipoglikemia. 8,9 Preeklamsia dan obesitas pada wanita hamil masing-masing secara independen terkait dengan hasil neonatal yang lebih buruk, memiliki kedua faktor tersebut dapat menunjukkan peningkatan tingkat hasil neonatal yang lebih buruk dibandingkan dengan adanya obesitas atau preeklamsia saja. 9 Namun kurangnya data mencakup kombinasi hal ini di Rumah Sakit Hasan Sadikin membuat peneliti tertarik melakukan penelitian untuk mempelajari kombinasi kehadiran obesitas dan preeklamsia pada wanita hamil terhadap luaran bayi dan lama perawatan di Rumah Sakit Hasan Sadikin periode 1 Januari 2015 -30 November 2019.…”
Section: Pendahuluanunclassified